2017
DOI: 10.1007/s11046-017-0172-2
|View full text |Cite
|
Sign up to set email alerts
|

Pneumocystis jirovecii and Cystic Fibrosis in Brittany, France

Abstract: Pneumocystis jirovecii is a transmissible fungus with a high pulmonary tropism. The prevalence of P. jirovecii in patients with cystic fibrosis (CF) has been estimated in Germany at 7.4%, in Spain at 21.5% and in Brazil at 38.2%. Data on the prevalence of P. jirovecii in CF patients in France remain scarce, particularly in Brittany, where the prevalence of CF is high (from 1/1600 to 1/4500). Our objectives were to determine the prevalence of colonization of the airways by P. jirovecii in Brittany in CF patient… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
24
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 15 publications
(26 citation statements)
references
References 32 publications
1
24
1
Order By: Relevance
“…This includes prophylaxis with fluconazole for Candida , acyclovir for herpes simplex virus, valganciclovir for cytomegalovirus (guided by the recipients’ and the donors’ status), and with trimethoprim‐sulfamethoxazole for Pneumocystis jiroveci . Prophylaxis for P. jiroveci is prudent given reports, primarily from Europe, describing colonization with P. jiroveci in CF patients . Additionally, for individuals with CF, some experts recommend a course of antibiotics targeting recently detected pulmonary pathogens immediately following transplant.…”
Section: Postoperative Management In Lt For Cf Patientsmentioning
confidence: 99%
“…This includes prophylaxis with fluconazole for Candida , acyclovir for herpes simplex virus, valganciclovir for cytomegalovirus (guided by the recipients’ and the donors’ status), and with trimethoprim‐sulfamethoxazole for Pneumocystis jiroveci . Prophylaxis for P. jiroveci is prudent given reports, primarily from Europe, describing colonization with P. jiroveci in CF patients . Additionally, for individuals with CF, some experts recommend a course of antibiotics targeting recently detected pulmonary pathogens immediately following transplant.…”
Section: Postoperative Management In Lt For Cf Patientsmentioning
confidence: 99%
“…Identification of P jirovecii in CF patients is described throughout the world, with regional differences appreciated. French studies describe a prevalence of P jirovecii of 2.5–12.5%, while a cohort of Brazilian CF patients had a prevalence of 38.2% …”
Section: Epidemiologymentioning
confidence: 99%
“…These two case presentations indicated that the recovery of some fungi like E. dermatitidis in patients with bronchiectasis should lead to search for a mild form of CF [10]. Nevez et al [11] detail the extensive laboratory processes setup in Brittany for the demonstration of Pneumocystis jirovecii in CF patients. The prevalence of Pneumocystis jirovecii was found to be 2.5% in Brittany despite the overall higher prevalence of CF in the population [11].…”
mentioning
confidence: 99%
“…Nevez et al [11] detail the extensive laboratory processes setup in Brittany for the demonstration of Pneumocystis jirovecii in CF patients. The prevalence of Pneumocystis jirovecii was found to be 2.5% in Brittany despite the overall higher prevalence of CF in the population [11]. The authors also describe successful genotyping of P. jirovecii in two of the three instances to set the stage for future evaluation of links between genotype evolution and virulence [11].…”
mentioning
confidence: 99%
See 1 more Smart Citation